Chapter Traducir al español el léxico de los castillos y fortalezas de Emilia-Romaña - Pano Alamán, Ana (Lessico multilingue dei Beni Culturali, 2023)
This chapter presents the results of a qualitative contrastive analysis of the Italian and Spanish terminology of medieval and Renaissance architecture. The study focuses on a corpus of Italian texts on the castles of the House of Este published on the TourER website, a project for the promotion of the architectural and landscape heritage of the Emilia-Romagna region. The chapter focuses attention on the most frequent multiword terms and expressions and a selection of concordances extracted from a learner aligned parallel corpus of Italian-Spanish translation. This chapter investigates translation strategies adopted in relation to the typology of texts and their potential readership.